Sol/gel transition of thermoresponsive Hyaluronan: From liquids to elastic and sticky materials. (15th June 2023) - Barbier, L.; Protat, M.; Pipart, P.; Marcellan, A.; Tran, Y.; Hourdet, D.
Abstract: Thermoassociating copolymers were prepared by grafting temperature responsive poly( N -isopropylacrylamide- stat - N - tert -butylacrylamide) telomers onto hyaluronan. By varying the composition of LCST side chains, from 50 to 100 wt% of NIPAM units, it is shown that the sol/gel transition of entangled solutions can be accurately controlled in the range of 10 to 35 °C with an abrupt transition and reversible properties. Complementary experiments, performed by DSC and NMR, demonstrate the close relationship between thermoassociation of LCST grafts, forming microdomains of low mobility, and macroscopic properties. Moreover, by performing tack experiments during heating we demonstrate that hyaluronan formulations abruptly switch from a weak adhesive viscous behavior to an elastic adhesive profile in the gel regime. As LCST side-chains form concentrated micro-domains of low mobility, physical gels can resist to dissociation above their sol/gel transition for relatively long periods when immersed in excess physiological medium. The thermoassociative behavior of these copolymers, whose properties can be finely tuned in order to form sticky gels at body temperature, clearly demonstrates their potential in biomedical applications such as injectable gels for drug delivery or tissue engineering. Graphical abstract: Unlabelled Image